PERSONNEL RESISTANCE TO CHANGES AS A REACTION TO THE STATE OF RISK AND UNCERTAINTY - N. Chetverikova (Вестник университета)
Organizational changes are accompanied by various processes that determine the outcome of the transformation. The author investigates such phenomenon as resistance of the personnel with its versatility in the modern world of management. The article presents the reasons and the most popular forms of resistance to organizational changes, according to the author. Riskiness and uncertainty in the situation of change exacerbate individual resistance. In this regard, emphasis was placed on the need to create a subsystem for managing personnel resistance in the situation of organizational changes. A project to overcome the resistance of the sta in the organization.